Physiological Effects of Water Flow Induced Swimming Exercise in Seabream Sparus aurata - Palstra, Arjan P.; Roque, Ana; Kruijt, Leo; Jéhannet, Pauline; Pérez-Sánchez, Jaume; Dirks, Ron P. (Frontiers in Physiology, 2020)
A longer on-land rearing period of Gilthead seabream Sparus aurata before transfer to sea-cages would allow the farmer to benefit from exercise-enhanced growth, resilience and robustness as induced by increasing water flow in the tanks. In this study, the physiological effects of flow-conditioning were investigated by subjecting large groups of experimental fish to minimal flow or to flow regimes inducing swimming exercise at 1 or 2 Body Length (BL) s-1 for a period of 8 months (Feb.-Oct.) in 1,500 l tanks. Fish representing the three treatment groups were then used for: (1) a stress challenge netting test and plasma cortisol measurement (baseline, peaking and recovery levels); (2) blood plasma measurements of glucose, triglycerides, lactate, cholesterol, growth hormone (GH) and insulin-like growth factor 1 (IGF1), and heart and muscle gene expression of the GH and IGF1 receptors and the muscle transcriptome by deep RNA sequencing (RNAseq). Fish size after eight months of flow conditioning was 92 ± 27 g body weight (BW) for fish under minimal flow; 106 ± 24 g BW (+15%) at 1 BL s-1, and 125 ± 27 g BW (+36%) at 2 BL s-1. Flow conditioning at 1 BL s-1 provided optimal conditions for growth and uniformity, but also stress (lowest baseline plasma cortisol), robustness (higher condition factor, larger hearts) and energy mobilization (increased plasma glucose). Although flow enhanced growth linearly with swimming speed, also the percentage of lordotic fish increased with exercise, particularly high for swimming at 2 BL s-1. The absence of important differences in plasma GH and IGF1, and expression levels of their receptors in heart and white skeletal muscle, indicated that other factors may be involved in growth enhancement. RNAseq of the white skeletal muscle showed up-regulated expression of genes involved in muscle contraction, muscle development and its molecular regulation, and immune genes that may play a role in the muscle repair mechanism. An exercise regime of swimming at 1 BL s-1 can be considered as optimal for farming robust seabream although the increase of skeletal deformities should be avoided.